PENERAPAN MEDIA PETA KERAGAMAN BUDAYA UNTUK MENINGKATKAN PEMAHAMAN RAGAM BUDAYA PADA KELAS II SD NEGERI 065853 MEDAN: Penelitian Tindakan Kelas - Rahmah Ramadhani; Asrar Aspia Manurung; Ruth Tiarma Manik (STKIP Subang, 2025)
This study aims to improve students' understanding of the concept of cultural diversity in Indonesia through the implementation of the Cultural Diversity Map media in Grade II of SD Negeri 065853 Medan. The research employed a Classroom Action Research (CAR) approach carried out in two cycles, each consisting of planning, action, observation, and reflection stages. The results indicate a significant improvement in students’ comprehension after using the map media. The average post-test score increased from 67.25 in cycle I to 80.22 in cycle II, and learning mastery rose from 59.09% to 82%. The Cultural Diversity Map was proven to be effective in providing a concrete and enjoyable learning experience, while also supporting the visual and kinesthetic learning styles common in elementary school students. These findings suggest that the use of map media is an appropriate alternative in teaching Pancasila Education, especially on cultural diversity topics in primary schools.